Real‐world effectiveness and safety of ombitasvir/paritaprevir/ritonavir ± dasabuvir ± ribavirin in hepatitis C: AMBER study. Issue 9 (9th September 2016) - Flisiak, R.; Janczewska, E.; Wawrzynowicz‐Syczewska, M.; Jaroszewicz, J.; Zarębska‐Michaluk, D.; Nazzal, K.; Bolewska, B.; Bialkowska, J.; Berak, H.; Fleischer‐Stępniewska, K.; Tomasiewicz, K.; Karwowska, K.; et al.
Summary: Background: Virologic and safety outcomes of ombitasvir/paritaprevir/ritonavir ± dasabuvir ± ribavirin (OBV/PTV/r ± DSV ± RBV) therapy have shown high sustained virologic response (SVR) rates and good tolerability in most patient populations in pre‐registration studies. Aim: To confirm these clinical trial findings in the treatment of genotype 1 and 4 hepatitis C under real‐world conditions. Methods: Patients enrolled for treatment with OBV/PTV/r ± DSV ± RBV based on therapeutic guidelines were included, and the regimen was administered according to product characteristics. Clinical and laboratory data, including virologic response, were collected at baseline, end of treatment (EOT) and 12 weeks after EOT. Results: A total of 209 patients with chronic hepatitis C were enrolled, most were genotype 1b‐infected (84.2%) and 119 (56.9%) had liver cirrhosis. Among these, 150 (71.7%) had failed previous anti‐viral therapies and 84 (40.2%) were null‐responders. At 12 weeks after EOT, SVR was achieved by 207 (99.0%) patients, ranging from 96.4% to 100.0% across subgroups. All Child–Pugh B and post‐orthotopic liver transplantation patients achieved SVR. Adverse events occurred in 151 (72.2%) patients and were mostly mild and associated with the use of RBV. Serious adverse events, including hepatic decompensation, renal insufficiency, anaemia, hepatotoxicity and diarrhoea, were reported in eight (3.8%) patients. In five (2.4%) patients, adverse events led to treatment discontinuation. On‐treatment decompensation was experienced by seven (3.3%) patients. Conclusions: The results of our study confirm previous findings. They demonstrate excellent effectiveness and a good safety profile of OBV/PTV/r± DSV±RBV in HCV genotype 1‐infected patients treated in the real‐world setting.